Lessons learned from the implementation of an online infertility community into an IVF clinic's daily practice. (2nd October 2015) - Aarts, Johanna W. M.; Faber, Marjan J.; Cohlen, Ben J.; Van Oers, Anne; Nelen, WillianNe L. D. M.; Kremer, Jan A. M.
Abstract : The Internet is expected to innovate healthcare, in particular patient-centredness of care. Within fertility care, information provision, communication with healthcare providers and support from peers are important components of patient-centred care. An online infertility community added to an in vitro fertilisation or IVF clinic's practice provides tools to healthcare providers to meet these. This study's online infertility community facilitates peer-to-peer support, information provision to patients and patient provider communication within one clinic. Unfortunately, these interventions often fail to become part of clinical routines. The analysis of a first introduction into usual care can provide lessons for the implementation in everyday health practice. The aim was to explore experiences of professionals and patients with the implementation of an infertility community into a clinic's care practice. We performed semi-structured interviews with both professionals and patients to collect these experiences. These interviews were analyzed using the Normalisation Process Model. Assignment of a community manager, multidisciplinary division of tasks, clear instructions to staff in advance and periodical evaluations could contribute to the integration of this online community. Interviews with patients provided insights into the possible impact on daily care. This study provides lessons to healthcare providers on the implementation of an online infertility community into their practice.